Green turtles illegal trade based on commercial law and state administrative law perspectives - Siahaan, Nomensen Freddy; Wati, Agustina (Indonesian Journal of Multidisciplinary Science, 2024)
Environmental ecosystems are the most important element in human life. Without a beautiful and healthy environment, humans will not live well. However, humans are greedy for the sustainability of environmental ecosystems, such as the illegal trade in green turtles that are not revealed to the public. This illegal trade disrupts the cycle of life and has a vast network, which is allegedly more numerous. This paper is a Normative Legal Research.  Normative Legal Research is a scientific procedure to find the truth based on the logic of the normative legal scientific. The scientific logic of normativeLegal Research is developed by the scientific concentrate and ways of thinking of normative jurisprudence and their objects are regulation themselves. In this case, both parties acting as Debtors and Creditors, namely the Seller and Buyer of Sea Turtles, have reached an agreement and fulfilled the elements of the agreement. Green turtles are animals that maintain the survival of seagrass and seaweed, which are protected by several regulations.